Magnetic Microscopy of Nanostructures - Hopster, Herbert; Oepen, Hans Peter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
This volume contains a comprehensive collection of overview articles on novel microscopy methods for imaging magnetic structures on the nanoscale. Written by leading scientists in the field the book covers synchrotron based methods, spin polarized electron methods, and scanning probe techniques. It will be a valuable source of reference for graduate students and newcomers to the field.
Imaging Magnetic Microspectroscopy -- Study of Ferromagnet-Antiferromagnet Interfaces Using X-Ray PEEM -- Time Domain Optical Imaging of Ferromagnetodynamics -- Lorentz Microscopy -- Electron Holography of Magnetic Nanostructures -- SPLEEM -- SEMPA Studies of Thin Films, Structures, and Exchange Coupled Layers -- Spin-SEM of Storage Media -- High Resolution Magnetic Imaging by Local Tunneling Magnetoresistance -- Spin-Polarized Scanning Tunneling Spectroscopy -- Magnetic Force Microscopy: Images of Nanostructures and Contrast Modeling -- Magnetic Force Microscopy — Towards Higher Resolution -- Scanning Probe Methods for Magnetic Imaging.
Keywords: Nanotechnology; Optical materials; Electronic materials; Metals; Condensed matter; Engineering; Nanotechnology; Optical and Electronic Materials; Metallic Materials; Condensed Matter Physics; Engineering, general